Neighborhood social capital and self-rated mental health: Disparities between migrants and native residents in Beijing - Wang, Xiaomeng; Zhou, Peiling; Liu, Zhilin (Frontiers in Public Health, 2022)
Introduction Although the impact of neighborhood social capital on mental health has long been recognized, the extent to which the impact differs between immigrants and local residents remains a puzzle. This study aims to bridge the gap by comparing internal migrants who are restricted by their household registration (hukou) status, and urban natives in China. Methods Using self-rated mental health and social capital survey data collected in 26 neighborhoods in Beijing, this study examines the mental health outcomes of three types of neighborhood social capital, including social networks, shared norms and mutual trust, and social support. Results The study finds that the hukou status of immigrants moderates the effect of neighborhood social capital on mental health, and that the internal migrants in China experience less mental health benefit of neighborhood social capital than urban natives. Compared with urban natives, neighborhood social networks have less positive effect on migrants' mental health than that of urban natives. Conclusion The findings suggest that policy makers can improve the mental health of migrants through social capital building on the premise of eliminating the restrictions of hukou system on the migrants' right to participate in neighborhood activities and to access neighborhood services.